Upaya Pencegahan dan Penanganan Stunting Melalui Penyuluhan di Wilayah Puskesmas Porong Sidoarjo - Djunawan, Achmad; Rizki, Muhammad Risya; Oktavia, Chindy (Jurnal Abdimas Jatibara, 2025)
SDGs (Suistainable Development Goals) number 2 say that eliminating all forms of malnutrition, including nutritional problems such as stunting. Based on data collected from the e-PPGBM application, the number of stunting reached 23.9% in Sidoarjo and 28% in the Porong primary health care working area. Therefore, there needs to be community service efforts for this problem. This community service activity aims to increase the knowledge of mothers in the Porong Primary Health Care area about predicting the height and weight of toddlers as well as how to prevent and deal with stunting. The activity method takes the form of counseling, practice predicting the height or length of toddlers, the weight of toddlers, and questions and answers. The implementer also provided pretest and posttest questionnaires before and after delivering the material to assess the increase in respondents' understanding. Implementation of service activities on 6 December 2023 at Porong Primary Health Care, Sidoarjo. The targets are mothers who have babies and toddlers who are indicated to be stunted in the work area of the Porong Sidoarjo Primary Health Care. The results of the paired T test from the pretest and posttest scores show a value of 0.00, meaning there is a difference between the pretest score and the posttest score. The conclusion from these results is that there is an increase in respondents' knowledge about predicting and treating stunting.